Updated results from a matching-adjusted indirect comparison of efficacy outcomes for ciltacabtagene autoleucel in CARTITUDE-1 versus idecabtagene vicleucel in KarMMa for the treatment of patients with relapsed or refractory multiple myeloma. (2nd January 2023) - Martin, Tom; Usmani, Saad Z.; Schecter, Jordan M.; Roccia, Tito; Jackson, Carolyn C.; Deraedt, William; Yeh, Tzu-min; Banerjee, Arnob; Pacaud, Lida; Garrett, Ashraf; Bartlett, Meaghan; Haltner, Anja; et al.
Abstract: Objective: This study used the latest available data cuts from the CARTITUDE-1 and KarMMa clinical trials to update previously published matching-adjusted indirect treatment comparisons (MAICs) assessing the comparative efficacy of ciltacabtagene autoleucel (cilta-cel) versus the FDA-approved idecabtagene vicleucel (ide-cel) dose range of 300 to 450 × 10 6 CAR-positive T-cells in the treatment of patients with relapsed or refractory multiple myeloma (RRMM) who were previously treated with a proteasome inhibitor, an immunomodulatory drug, and an anti-CD38 monoclonal antibody (i.e. triple-class exposed). Methods: MAICs were performed with the latest available individual patient data for cilta-cel (CARTITUDE-1) and published summary-level data for ide-cel (KarMMa). The analyses included treated patients from CARTITUDE-1 who satisfied the eligibility criteria for KarMMa. The MAIC adjusted for unbalanced baseline covariates of prognostic significance identified in the literature and by clinical expertise. Comparative efficacy was assessed for overall response rate (ORR), complete response or better (≥CR) rate, duration of response (DoR), progression-free survival (PFS), and overall survival (OS). Results: Cilta-cel was associated with statistically significantly improved ORR (odds ratio [OR]: 94.93 [95% confidence interval [CI]: 21.86, 412.25; p < .0001]; relative risk [RR]: 1.34), ≥CR rate (OR: 5.65 [95% CI: 2.51, 12.69; p < .0001]; RR: 2.23), DoR (hazard ratio [HR]: 0.52 [95% CI: 0.30, 0.88; p = .0152]), PFS, (HR: 0.38 [95% CI: 0.24, 0.62; p < .0001]), and OS (HR: 0.43 [95% CI: 0.22, 0.88; p = .0200]) compared with ide-cel. Conclusions: These analyses demonstrate improved efficacy with cilta-cel versus ide-cel for all outcomes over longer follow-up and highlight its therapeutic potential in triple-class exposed RRMM patients.